2006
DOI: 10.1002/ijc.22156
|View full text |Cite
|
Sign up to set email alerts
|

SULT1A1 genotype and susceptibility to colorectal cancer

Abstract: Several procarcinogens that are present in cooked red meat and tobacco smoke are substrates for sulfotransferase 1A1 (SULT1A1). The association between environmental exposures and colorectal cancer risk may be modified by individual differences in the metabolism. Thus, we investigated the effect of a common polymorphism in the SULT1A1 gene associated with decreased enzyme activity on the susceptibility to colorectal cancer in a populationbased case-control study. Patients (505) and 604 age-and sexmatched contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 39 publications
1
22
0
Order By: Relevance
“…The sulfonation of estrogens was catalyzed by SULT1A1 to form water-soluble and biologically inactive estrogen sulfates, which reducing the level of estrogen exposure in their target tissues [9,10]. Previous functional studies have demonstrated that the variant A allele is associated with significantly reduced sulfotransferase activity in platelets compared with the wild-type G allele [5,6] The relevant SULT1A1 Arg 213 His single-nucleotide polymorphism studies have shown that 213 His allele is linked to cancer susceptibility in several cancers [11][12][13][14][15]. The specific role of SULT1A1 codon 213 polymorphism in breast cancer susceptibility has been the research focus of numerous researches [11,[16][17][18][19][20][21][22][23][24][25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 97%
“…The sulfonation of estrogens was catalyzed by SULT1A1 to form water-soluble and biologically inactive estrogen sulfates, which reducing the level of estrogen exposure in their target tissues [9,10]. Previous functional studies have demonstrated that the variant A allele is associated with significantly reduced sulfotransferase activity in platelets compared with the wild-type G allele [5,6] The relevant SULT1A1 Arg 213 His single-nucleotide polymorphism studies have shown that 213 His allele is linked to cancer susceptibility in several cancers [11][12][13][14][15]. The specific role of SULT1A1 codon 213 polymorphism in breast cancer susceptibility has been the research focus of numerous researches [11,[16][17][18][19][20][21][22][23][24][25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 97%
“…Of the various polymorphisms in SULT1A1, the Arg-His polymorphism at position 213, in exon 7 (SULT1A1*2), has a twofold lower catalytic activity and thermo stability than its high-activity Arg 213 counterpart as demonstrated in platelet cytosol (Raftogianis et al, 1997;Nowell et al, 2000;Nagar et al, 2006). Although several reports show risk association of the SULT1A1 variant with different cancers (Sun et al, 2005;Dandara et al, 2006;Pachouri et al, 2006;Fan et al, 2007;Lilla et al, 2007;Bardakci et al, 2008), others show either no effect (Sellers et al, 2005) or a protective effect .…”
mentioning
confidence: 99%
“…Taking into account the SULT1A1 genotype, a significant risk increase associated to frequent meat consumption is observed in carriers of the SULT1A1*2 allele while in subjects with the SULT1A1*1/*1 genotype no association is apparent (Lilla et al, 2006). This differential effect is pronounced in individuals consuming mostly fried/grilled meat or processed meat but not in those preferring boiled/stewed meat.…”
Section: Colorectal Cancersmentioning
confidence: 83%